2008
DOI: 10.1093/cercor/bhn112
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Brain Maturation and Growth Patterns in C57BL/6J Mice via Computational Neuroanatomy of Diffusion Tensor Images

Abstract: Diffusion Tensor magnetic resonance imaging and computational neuroanatomy are used to quantify postnatal developmental patterns of C57BL/6J mouse brain. Changes in neuronal organization and myelination occurring as the brain matures into adulthood are examined, and a normative baseline is developed, against which transgenic mice may be compared in genotype-phenotype studies. In early postnatal days, gray matter-based cortical and hippocampal structures exhibit high water diffusion anisotropy, presumably refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 41 publications
5
59
0
Order By: Relevance
“…During brain mouse development, there are two contrasting phenomena that can be observed through changes in FA values (Verma et al, 2005; Baloch et al, 2009): i) a decrease of FA values in Gray Matter (GM) cortical structures reflecting the transition of the cortex from a highly columnar organization, encoded by radially oriented tissue anisotropy, to an organization characterized by a decrease in anisotropy due to the development of cortical dendrites; and ii) an increase of FA values in White Matter (WM) structures reflecting progressive development and myelination of axons towards establishing more organized axonal pathways.…”
Section: Resultsmentioning
confidence: 99%
“…During brain mouse development, there are two contrasting phenomena that can be observed through changes in FA values (Verma et al, 2005; Baloch et al, 2009): i) a decrease of FA values in Gray Matter (GM) cortical structures reflecting the transition of the cortex from a highly columnar organization, encoded by radially oriented tissue anisotropy, to an organization characterized by a decrease in anisotropy due to the development of cortical dendrites; and ii) an increase of FA values in White Matter (WM) structures reflecting progressive development and myelination of axons towards establishing more organized axonal pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with long disease duration are exposed to chronic stress, which has been demonstrated to contribute to frontostriatal degeneration and reductions in the length and branch numbers of apical dendrites, 92 and these changes could in turn present with a relative increase in the FA. 34,93 Without the confounding influences of illness duration and previous antidepressant treatment, we suggest that FA reductions in the genu of the CC and right anterior thalamic projections are more likely to be directly associated with the disease. Supporting our findings, some investigations have shown that FA abnormalities in genu of the CC and anterior thalamic projections might represent important markers of early-onset depression.…”
Section: Differential Findings Between the Subgroup Analysesmentioning
confidence: 86%
“…The development of the cerebral architecture including cell division and migration, axonal and dendritic sprouting and sorting-out, as well as final myelination of fiber tracts continues in humans and rodents after birth (13). In a recent MRI study using diffusion tensor imaging, fiber maturation of the corpus callosum reached a plateau ∼30-40 d after birth (14). The global biochemical composition of the brain parenchyma was shown to largely change during the first 60 d after birth with an increase of proteolipid protein and myelin basic protein (MBP), peaking at 10-18 d of age (15).…”
Section: Discussionmentioning
confidence: 99%